The Effectivity of Dental Health Education for Boarding School Students Using Audiovisual Media - Rr Pipiet Okti Kusumastiwi; Salsabila Usman (HM Publisher, 2023)
This study aimed to determine the effectiveness of audiovisual media in increasing students' knowledge and attitudes toward dental health in the Islamic boarding school, Yogyakarta, Indonesia. This study is a quasi-experimental study with a pre-posttest design approach. The target population was composed of students enrolled in 7th grade of an Islamic boarding school in Yogyakarta. A total of 82 students took part in this study. The students were assessed on their knowledge and attitudes before being given intervention through a pre-test questionnaire. An intervention was carried out by watching 10 minutes educational video on the main oral health preventive measures, including guidelines on diet and oral hygiene. The students watched the video 7 times for 7 days. After the intervention was given, then an assessment of knowledge and attitudes was carried out after being given the intervention using a post-test questionnaire. The knowledge aspect of the research subjects showed an increase in scores before the intervention with audiovisual media compared to after the intervention. This study also showed that the attitude aspect of the research subjects towards oral health showed an increase in scores before the intervention with audiovisual media compared to after the intervention. In conclusion, audiovisual media effectively increases knowledge and attitudes related to dental and oral health in students of Islamic boarding school in Yogyakarta, Indonesia.